Internet connectivity disruption in Switzerland (Switzerland) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Switzerland. Data sourced from IODA.
Network Disruption Incident ID: CH-2026-0003. Severity: critical. Confidence: 65%